Analisis Perilaku Pro Sosial Anak dalam Film Animasi Upin dan Ipin - Istiqomah Respatiari; Suryadi Suryadi (ALSYS, 2026)
Although the animation Upin and Ipin has been widely studied as a medium for character education, research that specifically discusses the representation of children’s prosocial behavior in particular episodes remains limited. This study aims to analyze the forms and representation of children’s prosocial behavior in the animated film Upin and Ipin Season 15 episode “Gerobok Rezeki.” This study uses a qualitative approach with a descriptive-analytical content analysis design. The research subject was focused on one episode selected purposively. Data were collected through participatory observation of audio-visual content and documentation studies, and were then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that prosocial behavior in the episode is represented through three main indicators, namely helping, sharing, and cooperation. Helping behavior appears in Upin and Ipin’s interactions with family and community figures, sharing behavior is seen in peer relationships at TK Tadika Mesra, whereas cooperation is reflected in playing together and mutual assistance in facing problems in the village environment. This finding affirms that the episode “Gerobok Rezeki” not only contains moral values but also constructs prosocial behavior concretely and contextually. The conclusion of this study affirms the importance of helping, sharing, and cooperation as foundations for the formation of children’s social character. The implications of this study indicate that the animation Upin and Ipin can be utilized as an educational medium for educators and parents in instilling empathy, care, and the ability to interact positively in early childhood.